Differential Ire1 determines loser cell fate in tumor-suppressive cell competition. - Zheng, J.; Guo, Y.; Shi, C.; Yang, S.; Xu, W.; Ma, X. (Cell reports, 2023)
Tumor-suppressive cell competition (TSCC) is a conserved surveillance mechanism in which neighboring cells actively eliminate oncogenic cells. Despite overwhelming studies showing that the unfolded protein response (UPR) is dysregulated in various tumors, it remains debatable whether the UPR restrains or promotes tumorigenesis. Here, using Drosophila eye epithelium as a model, we uncover a surprising decisive role of the Ire1 branch of the UPR in regulating cell polarity gene scribble (scrib) loss-induced TSCC. Both mutation and hyperactivation of Ire1 accelerate elimination of scrib clones via inducing apoptosis and autophagy, respectively. Unexpectedly, relative Ire1 activity is also crucial for determining loser cell fate, as dysregulating Ire1 signaling in the surrounding healthy cells reversed the "loser" status of scrib clones by decreasing their apoptosis. Furthermore, we show that Ire1 is required for cell competition in mammalian cells. Together, these findings provide molecular insights into scrib-mediated TSCC and highlight Ire1 as a key determinant of loser cell fate.